Development of Hybrid Culture-Based Tourist Attraction in Parijs Van Java - Fitra Ananta Sujawoto (Jurnal VOK@SINDO, 2014)
Bandung since the beginning of 20th century has benn known as Parijs van Java and has been visited by tourist, both domestic and foreign tourists. Bandung has unique tourist attractions, and most of the tourist attraction s produced by the revitalization of colonial heritage and local wisdom which have been developed by adopting modern elements that come through the process of globalization. Hybrid tourist attraction is not just merely creative tourist attraction. The existence of hybrid tourist attraction marks the presence of local resistance against the dominant culture. This research used literary study as a tool to collect the data. Meanwhile, descriptive-qualitative method combined with the postcolonial perspective was implemented to show how the hybrid attraction as a medium of local resistance. The results of this study indicate that there are at least four hybrid tourist attractions as the idea of renegotiation in cultural identity of local communities in the city of Bandung, which is hybrid historical tourist attraction, hybrid art tourist attraction, hybrid shopping tourist attraction, and hybrid culinary tourist attraction. Additionally, the result shows that the emergence of hybrid tourist attraction is caused by three factors, which is the experience of colonial history, global cultural flows, and the existence of the creative industries.